ANALYSIS OF FACTORS AFFECTING THE INCOME OF BATIK INDUSTRY MSMEs IN PAMEKASAN REGENCY - Hoirina, Arabela Sulfa; Titik, Crisanty Sutristyaningtyas; Vibriyanto, Norita (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the effect of capital, labor, financial inclusion, and financial literacy on the income of batik industry MSMEs in Pamekasan Regency. This research approach is quantitative using ordinal logistic analysis. The data in this study used primary data obtained through distributing questionnaires to batik business actors in Pamekasan Regency, and secondary data obtained from the Industry and Trade Office. The results showed that capital, labor, financial inclusion and financial literacy have a significant partial and simultaneous effect on MSME income in the Batik Industry in Pamekasan Regency. A one-level increase in the independent variable will increase to a higher income category. This study highlights the important role of capital, labor, financial inclusion and financial literacy in increasing the income of batik industry MSMEs. The increase in income of batik industry MSMEs is expected to improve community welfare and alleviate income inequality between rural and urban areas because the location of batik industry MSMEs in Pamekasan Regency is mostly in rural areas.